Aggregation and Conformational Changes in Native and Thermally Treated Polyphenol Oxidase From Apple Juice (Malus domestica) - Murtaza, Ayesha; Muhammad, Zafarullah; Iqbal, Aamir; Ramzan, Rabia; Liu, Yan; Pan, Siyi; Hu, Wanfeng (Frontiers in Chemistry, 2018)
This study investigated the effects of heat treatment after purification on dissociation, aggregation and structural modification of polyphenol oxidase (PPO) activity from apple (Malus domestica) juice. PPO activity at the 70 oC for 10min was still activated and drastically decreased since 20-60min with catechol and pyrogallol as substrate. Moreover, spectral results of fluorescence and circular dichroism (CD) indicated that increasing temperature for shorter and longer durations can cause reorganisation of the secondary structure of PPO and demolished the native configuration of PPO respectively. Compared with native PPO, all thermally treated PPO showed reduced activity with gradually increasing particle size shift towards section III of some fully assembled proteins treated at 70 oC for 10min (2670nm). Polyacrylamide gel electrophoresis (PAGE) analysis also exhibited the increase in protein content at the 70 oC for 10 min with molecular size 35 kDa (7.7±0.016c). Hence, thermally treated juice subjected to purification at high temperature for a short time could induce the aggregation of protein and is not really effective for PPO inactivation. For PPO, higher degree of long duration can induce the inactivation of the enzyme after processing.